ANALISIS FUNGSI BAHASA SEBAGAI SALAH SATU BENTUK KOMUNIKASI PADA NYANYIAN RAKYAT PAPUA - NFN, Normawati (Balai Bahasa Provinsi Papua, 2019)
The folksong of Papua is one of oral literature which contains many noble values in it. Therefore, it is necessary to preserve the folksong of the Papua, among others, by conducting a study of language functions. The purpose is to find out the various functions in the lyrics of Papuan folk songs as a form of communication in various languages in Papua. This research was conducted with a sociolinguistic approach that considered to how language is used so that it performs its functions maximally. The results of the study indicate that the language in the lyrics of the folksong of Papua has several functions, among other things, regulatory functions, interaction functions, personal functions, informative functions, and poetic functions.